MRI criteria for MS in patients with clinically isolated syndromes. - Montalban, X; Tintoré, M; Swanton, J; Barkhof, F; Fazekas, F; Filippi, M; Frederiksen, J; Kappos, L; Palace, J; Polman, C; Rovaris, M; de Stefano, N; et al. (2010)
In recent years, criteria for the diagnosis of multiple sclerosis (MS) have changed, mainly due to the incorporation of new MRI criteria. While the new criteria are a logical step forward, they are complex and-not surprisingly-a good working knowledge of them is not always evident among neurologists and neuroradiologists. In some circumstances, several MRI examinations are needed to achieve an accurate and prompt diagnosis. This provides an incentive for continued efforts to refine the incorporation of MRI-derived information into the diagnostic workup of patients presenting with a clinically isolated syndrome. Within the European multicenter collaborative research network that studies MRI in MS (MAGNIMS), a workshop was held in London in November 2007 to review information that may simplify the existing MS diagnostic criteria, while maintaining a high specificity that is essential to minimize false positive diagnoses. New data that are now published were reviewed and discussed and together with a new proposal are integrated in this position paper.